2001
DOI: 10.1159/000056222
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders in Burn Patients: A Follow-Up Study

Abstract: Background: We report on a prospective study of 45 patients with burn injuries admitted to a major burn unit in the greater Athens area. The study aimed to explore the prevalence of psychological and psychiatric disorders among burn survivors. Methods: The sample comprised all consecutive cases of adult burn patients in a 6-month period. Personal interviews were conducted by the administration of the Langner scale and the DSM-III-R Structured Clinical Interview. Twelve months later, 30 patients of the baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 15 publications
(53 reference statements)
5
57
1
3
Order By: Relevance
“…In an Australian sample, high levels of distress during a major brush fire was more strongly associated with PTSD symptoms than were sociodemographic or preexposure psychological variables (15). Finally, clinically significant symptoms of depression were reported by 23% in a US sample (16) and 27% in a British sample (17) at 2 years; and 20% of Greek patients with burn injuries had a depressive disorder at 2 years (10).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In an Australian sample, high levels of distress during a major brush fire was more strongly associated with PTSD symptoms than were sociodemographic or preexposure psychological variables (15). Finally, clinically significant symptoms of depression were reported by 23% in a US sample (16) and 27% in a British sample (17) at 2 years; and 20% of Greek patients with burn injuries had a depressive disorder at 2 years (10).…”
Section: Introductionmentioning
confidence: 87%
“…For example, acute stress disorder (ASD) has been reported in 18% to 26% in Greek (10), US (11), and Dutch (12) samples. Posttraumatic stress disorder (PTSD) has been observed in one third of Japanese (13) and US (11) samples between 3 and 6 months post burn, and 15% to 20% of Dutch (12) and Greek (10) samples at 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…20 Posttraumatic stress disorder was diagnosed in 17.8 and 20.0% of burn survivors at the baseline and the 12-month follow-up assessments, respectively. Logistic regression analysis revealed that face disfigurement was the only burn characteristic significantly associated with the presence of psychiatric morbidity.…”
Section: Discussionmentioning
confidence: 97%
“…In a review by Baur (76) comprising studies between 1986 and 1996, the prevalence rates of PTSD in adult burn populations varied between 31% and 45%. In more recent studies using self report instruments, frequencies vary between 2% (63) and 26% (82) within the 1 st month post burn and between 13% (65) and 33% (63) at the 12 months follow up. Using the SCID-Imethodology, Fauerbach et al (21) reported a prevalence of 8% at discharge from hospital and 20% at the 12-month follow up.…”
Section: Psychiatric Manifestation In Post Burn Patientsmentioning
confidence: 94%
“…[36] Finally, clinically significant symptoms of depression were reported by 23% in a US sample [37] and 27% in a British sample [38] at 2 years; and 20% of Greek patients with burn injuries had a depressive disorder at 2years. Malt et al and Patteron et al (62,18) reported that anxiety and depression were the most prevalent disturbances in burn patients at follow-up.It was found that symptoms of depression and anxiety generally occurred together, With prevalence rats between 25% and 65% one yr post burn, and that most symptoms subsided after that period (18) In more recent studies published after 1990, depression prevalence rates vary between 2% (63) and 53% (64) the 1 st month after the burn, and between 13% (65) and 34% (64) at 12 momth post burn. In a study from US by Fauerbach et al (21) ,the structured clinical Interview for DSM-III-R psychiatrc 18 disorders was utilized to diagnose major depression.…”
Section: Psychiatric Manifestation In Post Burn Patientsmentioning
confidence: 99%